2011
DOI: 10.1007/978-94-007-1192-1_40
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dry and Flood Turning in Terms of Dimensional Accuracy and Surface Finish of Turned Parts

Abstract: This work presents experimental and analytical results of a comparison of dry and flood turning in terms of dimensional accuracy and surface finish of turned parts. Subsequently, the influence of independent input parameters on dimensional accuracy and surface finish characteristics is investigated in order to optimize their effects. Three techniques-traditional analysis, Pareto ANOVA, and the Taguchi method-are employed. Hardened alloy steel AISI 4340 has been selected as work material. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Experiments carried out by each study concluded with similar results, where cutting parameters, such as low cutting speed having no noticeable difference between dry and flood turning [15,20,26]. There were also other notable similarities within the results of the studies, where factors would be more beneficial in conjunction with other parameters.…”
Section: Cutting Parameterssupporting
confidence: 58%
See 1 more Smart Citation
“…Experiments carried out by each study concluded with similar results, where cutting parameters, such as low cutting speed having no noticeable difference between dry and flood turning [15,20,26]. There were also other notable similarities within the results of the studies, where factors would be more beneficial in conjunction with other parameters.…”
Section: Cutting Parameterssupporting
confidence: 58%
“…The surface finish also directly relates to and is an important measure of the overall quality of the part, as this influences the performance, mechanical properties and cost of production [20]. As [21] states "Surface quality significantly improves fatigue strength, corrosion resistance, or creep life", which stresses the importance of specifying surface requirements during design stages so that the tools maybe be set up appropriately to achieve it.…”
Section: Introductionmentioning
confidence: 99%
“…Marksberry and Jawahir (2008) developed a tool-wear=tool-life relationship model for near-dry machining (NDM) and applied their model in comparing the performance of NDM and dry machining of steel wheel rims in terms of tool wear and tool life. Rafai and Islam (2010) compared dry and flood turning of alloy steel AISI 4340 in terms of diameter error, circularity, and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…These cutting conditions are also believed to have significant effects on the quality of the machined parts. Since these cutting parameters can be chosen and controlled by the user and are reflected in the quality of machined parts, they are one of the important variable for investigating their effects on the quality of turned parts [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of parameters currently available for measuring the surface roughness value. In this study, arithmetic average, a height parameter, has been adopted to represent surface roughness, since it is the most frequently used and internationally accepted parameter [3].…”
Section: Introductionmentioning
confidence: 99%